Thermodynamic study of Butylamine + Propanone, + Methyl Isobutyl Ketone (MIK) at (288.15 to 318.15) K temperature range - Campos, Viviana del Valle (2017)
Experimental determination of density and viscosity of the pure components and [Butylamine (1) + Propanone (2)] and [Butylamine (1) + MIK (2)] binary mixtures at (288.15 to 318.15) K are performed using an Anton Paar SVM 3000/G2 Stabinger Viscometer. The excess molar volume and viscosity deviation are calculated. Correlation equations for the experimental data and calculated functions are obtained. For [Butylamine + Propanone] binary system, the excess molar volume is negative and the viscosity deviation is positive for all temperatures. The values of excess volumes become more negative and the deviations of viscosity more positive with increasing temperature. For [Butylamine + MIK] binary system, the excess molar volume and the viscosity deviation are sigmoid. The excess molar volume is negative and the viscosity deviation is positive until next molar fractions x1 ≈ 0.7.